Desertification Mapping in Western Rajasthan - Singh, Surendra; Kar, Amal; Joshi, D C; Ram, Balak; Kumar, Suresh; Vats, P C; Singh, N; Raina, P; Kolarkar, A S; Dhir, R P (Annals of Arid Zone, 2016)
Using the 1990 UNEP definition of desertification, an attempt was made to map the desertification hazards in western Rajasthan. The first stage involved the mapping of dominant land uses in different rainfall zones. This was followed by mapping of dominant and associate processes of desertification and their severity for desertification status.